Oracle Internals - Burleson, Donald (Auerbach Publications, 2017)
If you are a typical Oracle professional, you don't have the luxury of time to keep up with new technology and read all the new manuals to understand each new feature of the latest release from Oracle. You need a comprehensive source of information and in-depth tips and techniques for using the new technology. You need Oracle Internals: Tips, Tricks, and Techniques for DBAs. Oracle has evolved from a simple relational database into one of the most complex e-commerce platforms ever devised. It's not enough for you to understand just the Oracle database. You must also understand the components of the Web server technology, XML, Oracle Security, Oracle and Java, and a host of other issues in order to do your job properly. This book is a compendium of the best and most useful articles from Oracle Internals, Auerbach Publications' newsletter for Oracle database administrators and other Oracle professionals. Edited by Oracle guru Don Burleson, it provides the type of in-depth, highly technical information not found in any other book, information only available from peers and consultants. The chapters focus on the truly tough stuff - proven techniques learned in the trenches. You could get this information from other sources, but you'd have to hunt and peck for it. Can you afford that kind of time? Oracle Internals: Tips, Tricks, and Techniques for DBAs gives you knowledge and advice directly applicable to your work in one easy-to-use resource.